TEACHING CRITICAL READING THROUGH ONLINE - Sunani, Sunani; Nadjmudin, Muhammad; Yeni, Ely; Herman, Herman (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
The literacy ability of Indonesian children is lower than children in other countries. In addition, students' vocabulary mastery is low. Even though the teacher had given vocabulary instruction to the students during the reading comprehension class, they still translated the text word by word into Indonesian. This study analyzes the effect of online learning on the acquisition of critical reading among students. This study used a pre-experimental study without a control group. Tests for the validity and reliability of reading comprehension texts and vocabulary tests were conducted before the test involving 40 participants. The technique used to collect data is a test. Validity and reliability were measured using some of the same texts used as pre-test and post-test. The pre-test and post-test scores were analyzed by Wilcoxon statistical analysis to test their reading scores before and after the intervention on the same subjects. The findings from the t-test revealed that the critical reading intervention was beneficial for students. Further studies showed that the instructional intervention adopted could help them improve their reading comprehension performance. These findings are expected to provide a teaching model that responds to the typical rise of today's online learning.